The Effect of Attention on Repetition Suppression and Multivoxel Pattern Similarity - Moore, Katherine S.; Yi, Do-Joon; Chun, Marvin (Journal of cognitive neuroscience, 2013)
Fundamental to our understanding of learning is the role of attention. We investigated how attention affects two fMRI measures of stimulus-specific memory: repetition suppression (RS) and pattern similarity (PS). RS refers to the decreased fMRI signal when a stimulus is repeated, and it is sensitive to manipulations of attention and task demands. In PS, region-wide voxel-level patterns of responses are evaluated for their similarity across repeated presentations of a stimulus. More similarity across presentations is related to better learning, but the role of attention on PS is not known. Here, we directly compared these measures during the visual repetition of scenes while manipulating attention. Consistent with previous findings, we observed RS in the scene-sensitive parahippocampal place area only when a scene was attended both at initial presentation and upon repetition in subsequent trials, indicating that attention is important for RS. Likewise, we observed greater PS in response to repeated pairs of scenes when both instances of the scene were attended than when either or both were ignored. However, RS and PS did not correlate on either a scene-by-scene or subject-by-subject basis, and PS measures revealed above-chance similarity even when stimuli were ignored. Thus, attention has different effects on RS and PS measures of perceptual repetition.